KONTRIBUSI DANA BAGI HASIL MINYAK DAN GAS BUMI TERHADAP ANGGARAN PENDAPATAN BELANJA KABUPATEN (APBK) ACEH UTARA KAITANNYA DENGAN KEMISKINAN - Cut Asmaul Husna TR (Jurnal Ilmu Hukum, 2013)
Enacted Law No. 11 Year 2006 on theGoverning of Aceh, revenue-sharingarrangement on the oil and gas thatare part of government revenue fromthe mining Aceh gas by 30% "(thirtypercent). In addition, the Governmentof Aceh received additional miningrevenue sharing of oil by 55% (fiftypercent), and mining of natural gas by40% (forty percent). "This researchmoved from the initial understandingthat Indonesia is not yet optimal andconsistent in realizing the revenue-sharing oil and gas mining to Aceh.This study intends to gain anoverview of the contribution of theimplementation of the contractmining of oil and gas, the role of theGovernment of Aceh in realizing hasionpublicfundingforandimplementation of revenue-sharingfor the future of Aceh. This study is aqualitative research, socio-economicapproach. Data was collected byobservation of participants, in-depthinterview. Contribution of the study isexpected to be given in practice to theAceh Government and relatedinstitutions as well as theoretical research in filling shortagesNanggroe Aceh Darussalam.Keywords:Dana Bagi Hasil research in filling shortages Nanggroe Aceh Darussalam.Migas,Pendapatan in Daerah,Kemiskinan Lokal.